2015
DOI: 10.1111/hel.12250
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Diagnosis of Helicobacter pylori infection

Abstract: During the period reviewed, prevalence studies were essentially performed in less economically advanced countries and a high prevalence was found. The traditional risk factors for Helicobacter pylori positivity were mostly found. Transmission studied by molecular typing showed a familial transmission. The eventual role of water transmission was explored in several studies with controversial results. Concerning diagnosis, most of the invasive and noninvasive methods used for the diagnosis of H. pylori infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
126
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(142 citation statements)
references
References 57 publications
(72 reference statements)
4
126
1
7
Order By: Relevance
“…22 Other study found a prevalence of 68.3%, while a study conducted by Fonseca reported a prevalence of 53%, where 6 (75%) patients suffered from erosive gastritis and 2 (25%) patients suffered from superficial gastritis. 17,23 Another study even indicated a lower prevalence of 40.8%. 24 In this study, we found significant association between H. pylori infection and the severity of endoscopic appearances (OR = 2.67; 95% CI = 1.18-6.05).…”
Section: Discussionmentioning
confidence: 97%
“…22 Other study found a prevalence of 68.3%, while a study conducted by Fonseca reported a prevalence of 53%, where 6 (75%) patients suffered from erosive gastritis and 2 (25%) patients suffered from superficial gastritis. 17,23 Another study even indicated a lower prevalence of 40.8%. 24 In this study, we found significant association between H. pylori infection and the severity of endoscopic appearances (OR = 2.67; 95% CI = 1.18-6.05).…”
Section: Discussionmentioning
confidence: 97%
“…Gastroduodenoscopy is very essential in symptomatic individuals who are not responding to therapy and those aged older than 45 years according to European guidelines [20]. It is not only diagnostic but also therapeutic in upper gastrointestinal bleeding (UGIB) cases.…”
Section: Invasive Methodsmentioning
confidence: 99%
“…Furthermore, it is very informative regarding the degree of inflammation and even for categorizing post helicobacter infective gastric mucosal changes (atrophic gastritis, intestinal metaplasia, mucosa associated lymphoid tissue (MALT) lymphoma, malignancy) [28]. A biopsy sample from the body of the stomach is preferred compared to one from the antrum in patients taking acid suppressing drugs, or it can be performed after 2 weeks after drug discontinuation [5,20]. The availability of immunohistochemistry is limited; however, it has advantages in diagnosing HP infection in RUT negative cases and HP CagA genotypes [29,30].…”
Section: Histologymentioning
confidence: 99%
“…Almost half of the world's population has been infected with H. pylori, particularly in developing countries where people are more susceptible to the infection, mostly due to the large populations and poor sanitation (2,3).…”
mentioning
confidence: 99%